Mind the Gap: The Effects of Temporal and Spatial Separation in Localization of Dual Touches on the Hand - Sadibolova, Renata; Tamè, Luigi; Walsh, Eamonn; Longo, Matthew R. (Frontiers in Human Neuroscience, 2018)
In this study, we aimed to relate the findings from two predominantly separate streams of literature, one reporting on the localisation of single touches on the skin, and the other on the distance perception of dual touches. Participants were touched with two points, delivered either simultaneously or separated by a short delay to various locations on their left hand dorsum. They then indicated on a size-matched hand silhouette the perceived locations of tactile stimuli. We quantified the deviations between the actual stimulus grid and the corresponding perceptual map which was constructed from the perceived tactile locations, and we calculated the precision of tactile localisation (i.e. the variability across localisation attempts). The evidence showed that the dual touches, akin to single touch stimulations, were mislocalised distally and that their variable localisation error was reduced near joints, particularly near knuckles. However, contrary to single-touch localisation literature, we observed for the dual touches to be mislocalised towards the ulnar side of the hand, particularly when they were presented sequentially. Further, the touches presented in a sequential order were slightly ‘repelled’ from each other and their perceived distance increased, while the simultaneous tactile pairs were localised closer to each other and their distance was compressed. Whereas the sequential touches may have been localised with reference to the body, the compression of tactile perceptual space for simultaneous touches was related in the previous literature to signal summation and inhibition and the low-level factors, including the innervation density and properties of receptive fields of somatosensory neurons.